A molecular perspective on the systematics and distribution of Loxopholis lizards in South and Central America, with advances on the biogeography of the tribe Ecpleopodini (Gymnophthalmidae: Squamata). Issue 1 (31st December 2022) - Marques-Souza, Sergio; Pellegrino, Katia Cristina M.; Brunes, Tuliana O.; Rojas-Runjaic, Fernando J. M.; Rodrigues, Miguel Trefaut
Abstract : Knowledge about the biological diversification of vertebrates in the Amazonia has previously relied on taxa that diversified in relatively recent timeframes (i.e. Plio-Pleistocene). Dating of evolutionary events in small lizards and frogs, on the other hand, has progressively demonstrated that the major phylogenetic events in these organisms occurred earlier in time, from the Eocene to the Miocene, opening a window to reveal the Amazonia's landscape dynamics throughout ancient periods. Here we investigate the phylogenetic relationships, diversification times, and biogeography of Loxopholis, a diverse genus of small leaf-litter ecpleopodin lizards endemic to the Amazonia. In order to place Loxopholis diversity into a larger taxonomic perspective, we used statistical biogeographic methods (BioGeoBEARS) to reconstruct the biogeography of the Ecpleopodini tribe. We found that the evolution of the Ecpleopodini occurred mostly in the Amazonia's north region. Additionally, we found evidence that contacts between the Amazonia and the Atlantic Forest took place multiple times during the Cenozoic (earlier than previously proposed) and that these events influenced species colonization of open environments in South America via the Vanishing Refuge model. Our hypothesis on the evolution of Loxopholis, in contrast, suggests that multiple processes acted on the current species distribution, including three main dispersal events: the emergence of Lake Pebas, the rising of the Iquitos arch, the Andean orogeny and the emergence of the Panama Isthmus.